Sending a Signal from Paris : Transforming the Economy to Achieve Zero Net Emissions - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, focuses on economic policy as the key to mobilizing a coordinated global response to climate change. He talks about the need to confront climate change, without which there will be no hope of ending poverty or boosting shared prosperity. He adds that the longer the delay in tackling climate change, the higher the cost will be to do the right thing for our planet and our children. He affirms that from the Paris meeting we will make the rallying cry for effective management of local, national and global economies to fight climate change. The Paris agreement needs to speak as loudly of economic transformation as it does of pollution or carbon emissions targets. Carbon pricing that can raise revenues and can be used to generate more economic and social benefits. Specific efforts are needed to scale up renewable energy and develop carbon capture and sequestration technology, at a pace that will allow us to reach carbon neutrality by the end of the century. He concludes by saying that he will drive the World Bank Group and all its capabilities--financial, technical, and human--to support this development transition toward the goal of preserving our planet for all future generations.